Microbiome and Metabolic Changes of Milk in Response to Dietary Supplementation With Bamboo Leaf Extract in Dairy Cows - Jing-wei, Zhan; Yi-yuan, Shen; Xin, Li; Hua, Zhang; Hui, Niu; Luo-yun, Fang; Ben-hai, Xiong; Jin-jin, Tong; Lin-shu, Jiang (Frontiers in Nutrition, 2021)
Bamboo leaf extracts, with high content of flavonoids and diverse biological activities are used in animal husbandry. Increasing evidence has suggested an association between bovine physiology and the udder microbiome, yet whether the microbiota and metabolites of milk affect mammary gland health or milk quality remains unknown. Herein, we provide a potential mechanism for the effects of bamboo leaf extracts on milk microbiota and metabolites of dairy cows. Twelve multiparous lactating Chinese Holstein dairy cows were randomly separated into two groups: basal diet as control group (CON, n=6) and diet supplemented with 30 g/d bamboo leaf extract per head as AOB group (AOB, n=6) for 7 wk (2 wk adaptation, 5 wk treatment). Milk samples were collected at the end of the trial (wk 7) for microbiome and associated metabolic analysis by 16S rRNA gene sequencing and liquid chromatography-mass spectrometry (LC-MS). The results showed that milk protein was increased (p< 0.0001) and somatic cell count (SCC) showed a tendency to decrease (p = 0.09) with AOB supplementation. The relative abundance of Firmicutes was significantly decreased (p=0.04) while a higher relative abundance of Probacteria (p=0.01) was seen in the group receiving AOB compared to the CON group. The AOB group had a significantly lower relative abundance of Corynebacterium_1 (p = 0.01), Aerococcus (p = 0.01) and Staphylococcus (p = 0.02). There were 64 different metabolites significantly upregulated including glycerophospholipids and fatty acyls, and 15 significantly downregulated metabolites, such as moracetin, sphinganine and lactulose in the AOB group. Metabolic pathway analysis of the different metabolites revealed that the sphingolipid signalling pathway was significantly enriched, together with glycerophospholipid metabolism, sphingolipid metabolism and necroptosis in response to AOB supplementation. Several typical metabolites were highly correlated with specific ruminal bacteria, demonstrating a functional correlation between the milk microbiome and associated metabolites. These insights into the complex mechanism and corresponding biological responses highlight the potential function of AOB, warranting further investigation into the regulatory role of specific pathways in metabolism.